LEARNING OF REACTION RATE WITH NESTED CURRICULAR ARRANGEMENT TO IMPROVE CRITICAL THINKING SKILLS AND UNDERSTANDING THE CONCEPT OF STUDENTS IN ACTIVE-REFLECTIVE LEARNING - Omes, Maria Fransiska (JCER (Journal of Chemistry Education Research), 2019)
This study aims to evaluate the learning rate of reactions by nested curricular arrangement. This learning is designed using the inquiry model. The learning process was attended by 34 XI MIA 7 students of SMAN 1 Manyar, Gresik, East Java. The objects in this study are critical thinking skills and students' understanding of the concept of active-reflective learning styles. This study was designed using "pre-experimental design," using one group pretest-posttest design. Analysis of critical thinking skills is done using t-tests and students' understanding of concepts is done using the Wilcoxon test. Learning is carried out for 2 times with the smallest percentage of performance in each meeting that is 80%. This shows the learning process is going well. Critical thinking skills that are trained and measured consist of 4 elements, namely: interpretation, inference, analysis, and explanation with a calculated value of t = 26.991. This value indicates that t arithmetic> t table. This shows that there are significant differences in students' critical thinking skills before and after learning. In understanding the concept test value of Asymp Sig = 0.00. This value indicates that the Asymp Sig <0.05. It can be concluded that there is an increase in the conceptual understanding of active-reflective learning style students after following the reaction rate learning by nested curricular structuring.